Rzetelnosc i trafnosc prób Batak Lite sluzacych do oceny koordynacyjnych zdolnosci motorycznych zapasników - Gierczuk, D.; Bujak, Z. (Polish Journal of Sport and Tourism, 2014)
The aim of this work was to assess selected validity criteria of motor tasks included in Batak Lite. The tasks are used to control coordination motor abilities in athletes of different sports. Material and methods. Twenty male Greco-Roman wrestlers from the sports school SMS in Radom were included in the study. They were 17-18 years of age and their training experience was 4-7.5 years long. The validity of motor tasks was determined on the basis of two criteria, i.e. reliability and diagnostic accuracy. To define the reliability of the tests, the research was carried out twice with an interval of 5-7-days (test-retest). Diagnostic accuracy of selected indices was determined with the help of three main criteria. The analysis included 6 motor tasks performed with the use of Batak Lite. Results. Tests I, II, IV and V are characterised by reliability coefficients higher than 0.50 and, regardless of the assumed accuracy criterion, by coefficients higher than 0.30. Thus, they meet the validity requirements within the assessed criteria. The highest accuracy coefficients were observed in motor tests assessing quick reaction (r = 0.46-0.63), simple reaction including sensory (r = 0.61-0.78), motor (r = 0.33-0.46) and complex (r = 0.34-0.49) reactions as well as spatio-temporal orientation (r = 0.33-0.49) and movement coupling (r = 0.34-0.49). Conclusions. Four Batak Lite tests displayed sufficient reliability and diagnostic accuracy. Therefore, they can be implemented in the training process of wrestlers. The strongest correlation was noted between Batak Lite tests and motor tests that assessed quick reaction, spatio-temporal orientation and movement coupling.